2018
DOI: 10.1016/j.bcp.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the abilities of diverse nitroaromatic prodrug metabolites to exit a model Gram negative vector for bacterial-directed enzyme-prodrug therapy

Abstract: Gene-directed enzyme-prodrug therapy (GDEPT) employs tumour-tropic vectors including viruses and bacteria to deliver a genetically-encoded prodrug-converting enzyme to the tumour environment, thereby sensitising the tumour to the prodrug. Nitroreductases, able to activate a range of promising nitroaromatic prodrugs to genotoxic metabolites, are of great interest for GDEPT. The bystander effect (cell-to-cell transfer of activated prodrug metabolites) has been quantified for some nitroaromatic prodrugs in mixed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Importantly, our model informs directly on the relative abilities of prodrug metabolites to exit Gram negative bacterial activator cells. Using this technique we have observed that prodrugs can differ in their suitability for VDEPT versus BDEPT applications [3], which highlights the importance of evaluating enzyme-prodrug combinations in models relevant to the intended GDEPT vector. Taking into account the fundamental physiological differences associated with different gene-delivery systems will facilitate the identification of optimal enzyme-prodrug combinations for each setting as new vectors and prodrugs are developed.…”
Section: Additional Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, our model informs directly on the relative abilities of prodrug metabolites to exit Gram negative bacterial activator cells. Using this technique we have observed that prodrugs can differ in their suitability for VDEPT versus BDEPT applications [3], which highlights the importance of evaluating enzyme-prodrug combinations in models relevant to the intended GDEPT vector. Taking into account the fundamental physiological differences associated with different gene-delivery systems will facilitate the identification of optimal enzyme-prodrug combinations for each setting as new vectors and prodrugs are developed.…”
Section: Additional Informationmentioning
confidence: 99%
“…However for nonnitroaromatic prodrugs this incubation time may need to be optimised. For nitroreductase assays metronidazole has a negligible bacterial bystander effect [3] and can be used as a nil bystander control to compare to other prodrugs.…”
Section: Optimizing Prodrug Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that reduced metabolites of metronidazole, PR-104A, and SN27686 exhibited little cell to cell transfer while nitro-CBI-DEI and reduced metabolites of CB1954 passed it effectively. It was also demonstrated that 2-nitro reduction products showed substantially higher bystander effect as compared to 4-nitro reduction products [ 83 ]. Lehouritis et al exploited the natural enzymolome of the wild-type probiotic bacteria such as Escherichia coli Nissle, Bifidobacterium breve , Lactococcus lactis , and Lactobacillus species to activate multiple prodrugs owing to their safety.…”
Section: Mechanism Of Tumor Suppressionmentioning
confidence: 99%